William Woys Weaver: Sauerkraut Yankees - Davidson, Alan E (Petits Propos Culinaires, 2024)
William Woys Weaver: Sauerkraut Yankees (Pennsylvania German Foods and Foodways): University of Pennsylvania Press, 1983: 238 pp., many black and white illustrations, long and rich bibliography, full index, clothbound 25.00, paperback 12.50.